(untitled) (Revista Rupturas, 2016)
This article proposes both, a critical discussion and reflection about neoclassical economic theory, as a nowadays hegemonic paradigm in economics. It debates not only on the origins but also on the historical evolution of this theory, its epistemological and methodological bases, its theoretical results and its ethical bases. At the same time, it is offered a comparison with some aspects concerning Marxian theory, which is criticized in some of its most important propositions. This critical view is made from a Keynesian and post-Keynesian point of view, according with their epistemic and theoretical premises about uncertainty and complexity in economics. Some ethical considerations are made regarding the right for a dignifying life for every human being as a fundamental and inalienable right for everybody. This is an allegation against the dogmatism and against the abuse of the economics as a kind of totalitarian view, and in favor of an economic science that is able to know its limits and that works with the reality pursuing dignity in the life of every human being.